Pengetahuan, Sikap dan Dukungan Keluarga terhadap Niat Memeriksakan Dahak pada Presumtif TBC (Journal of Telenursing (JOTING), 2023)
This study aims to determine the relationship between knowledge, attitudes, and family support on the intention to have sputum examined in a group suspected of having tuberculosis in the Margoyoso II Health Center. The research method used in this research is quantitative. The design in this study is analytic with a cross sectional approach. The results showed that of the 113 respondents who had low knowledge about tuberculosis, 44 (67.7%) had a low attitude towards sputum examination, 47 (65.3%), and 55 (85.9%) had a low level of family support. Results The knowledge variable has a p value of 0.003, attitude has a p value of 0.006, family support has a p value